Perkembangan Mental Balita di Jawa Barat Berdasarkan Data Survei Kinerja dan Akuntabilitas Program KKBPK - Nasution, Ade Saputra; Suhenda, Dadang; Ekawati, Rindang (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
Mental development in toddlers that is not optimal can lead to mental retardation resulting in psychological disorders in children, disruption of toddlers' social relationships, and can also cause crimes when toddlers enter their teenage years such as alcohol, theft and other behavioral deviations. Examining the influence of factors on the use of contraceptives, mother's education and the ideal number of children on the mental development of toddlers in West Java. This study aims to analyze the influence of family participation in parenting and growth and development of toddlers and BKB in West Java Province. The study used an analytic survey method with a cross sectional design. Respondents were parents or families with toddlers and preschoolers in the BKB group and 2,803 were taken by purposive sampling and bivariate analysis using the Chi-Square test. The Results mother's education has a value of 0.036 so that it has an influence on the mental development of toddlers, the variable use of contraceptives has a value of 0.354 so it has no effect on the mental development of toddlers and the ideal number of children has a value of 0.101 so it has no influence on the mental development of toddlers in West Java. The number of children a family has can affect the mental development of toddlers, so that every family must have the ideal number of children so they can focus on the mental development of their children.